Preventing falls in aged care - Breitenmoser, Kurt.; Garner, Simon; Baricevic, Thomas; Scoglio, Stephen; Mouzakis, Steve; Tusia, Daniel; Video Education Australasia (Bendigo, Vic., 2009)
'In caring for the elderly - be it in community-based care or within a residential aged care facility - falls prevention is critical. Elderly people are often vulnerable to falls for a variety of reasons - it could be related to infirmness, compromised vision, slippery surfaces, ill-fitting footwear, lack of necessary physical support, being affected by medication, or a number of other factors. Furthermore, the physical injury that can occur with falls is generally exacerbated by age, and recovery times can be much longer compared with those for younger people who experience similar incidents. Knowing how to minimise the risk of falls is essential for any carer or other professional working in aged care.'
Introduction (1 min. 27 sec.) -- What is a fall? (4 min. 24 sec.) -- Identifying risk factors (4 min. 14 sec.) -- Falls prevention programs (Part I): identifying and assessment (4 min. 48 sec.) -- Falls prevention programs (Part II): implementation and risk control (4 min. 29 sec.) -- Conclusion [1] (46 sec.) -- Conclusion [2] (1 min.)
Producer, Kurt Breitenmoser ; executive producer, Simon Garner ; director, Thomas Baricevic ; writer, Stephen Scoglio.
Presenter, Steve Mouzakis ; mime, Daniel Tusia.
Keywords: Falls (Accidents) in old age -- Australia; Falls (Accidents) -- Australia -- Prevention; Nursing homes -- Australia -- Safety measures; Older people -- Care